2020
DOI: 10.1177/1758835920915303
|View full text |Cite
|
Sign up to set email alerts
|

Pazopanib as a possible option for the treatment of metastatic non-clear cell renal carcinoma patients: a systematic review

Abstract: Background: Effective systemic treatment of non-clear cell renal carcinoma (nccRCC) is still an unmet clinical need, with few studies to support an evidence-based approach. To date, the only recommended standard first-line treatment is sunitinib. Pazopanib may also be used in nccRCC but its place in therapy is not clearly established. It has comparable efficacy and better tolerability than sunitinib in clear cell renal carcinoma. Our objective was to review the use of pazopanib in metastatic nccRCC. Methods: W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Id-1 positive Id-1 negative Id-1 positive-rechecked Id-1 negative-rechecked cells, Ki-67 is a sign of the late-stage cell cycle. The mRNA level of Ki-67 is highest around the G2 phase, while its protein level increases throughout the cell cycle and reaches a peak during mitosis (11). At the same time, ki-67 was found to play a key role in mitosis by regulating recombinant chromatin, promoting epithelial mesenchymal transformation and thus inducing the occurrence and development of CCRCC.…”
Section: Discussionmentioning
confidence: 99%
“…Id-1 positive Id-1 negative Id-1 positive-rechecked Id-1 negative-rechecked cells, Ki-67 is a sign of the late-stage cell cycle. The mRNA level of Ki-67 is highest around the G2 phase, while its protein level increases throughout the cell cycle and reaches a peak during mitosis (11). At the same time, ki-67 was found to play a key role in mitosis by regulating recombinant chromatin, promoting epithelial mesenchymal transformation and thus inducing the occurrence and development of CCRCC.…”
Section: Discussionmentioning
confidence: 99%
“…[58][59][60][61][62] The trials found pazopanib to be well tolerated overall; however, CTCAE grade 3 adverse events were reported in 20% to 55% of patients, the most common being fatigue, diarrhea and hypertension. [58][59][60]63 However, interestingly, in a retrospective cohort study of patients with metastatic nccRCC treated with pazopanib or sunitinib, pazopanib was associated with inferior OS. 64 Thus, while TKI monotherapy has shown some clinical efficacy in nccRCC subtypes, there is much room for improvement.…”
Section: Pazopanibmentioning
confidence: 99%
“…Tumor ablation is a common non-vascular interventional tumor therapy and has been recommended by several guidelines for treating diverse solid tumors, for example, liver cancer and lung cancer [7][8][9][10][11][12][13][14]. The guidelines for the treatment of liver cancer recommend radiofrequency, cryotherapy, absolute alcohol injection, and microwave ablation (MWA) as local therapies [8].…”
Section: Background and Rationale {6a}mentioning
confidence: 99%